The Role of the Hidden Curriculum in Teaching the Arabic Language to Secondary School Students - إبراهيم, قتيبة أحمد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The current study aimed to explore the role of the hidden curriculum in teaching the Arabic language to preparatory stage students. The study adopted a descriptive survey method and utilized a questionnaire as the primary data collection tool. The instrument was administered to a purposefully selected sample of 95 male and female students during the second semester of the academic year 2024/2025. Frequencies, percentages, means, and standard deviations were calculated. The study reached several key findings, the most important of which are: The school environment and its activities play an effective role in shaping students’ cognitive, moral, and practical skills. The frequent use of Modern Standard Arabic by teachers positively influences the development of basic Arabic language skills. Engaging students in literary activities—such as organizing story-writing workshops and holding speech and poetry forums—strengthens their attachment to the Arabic language. Employing modern learning strategies in Arabic instruction enhances social values, supports speaking and listening skills, encourages openness to others’ opinions, and promotes peer collaboration. The study concluded with a number of recommendations based on the results obtained.